Internet Use and Psychological Wellness During Late Adulthood - Erickson, J.; Johnson, Genevieve (Cambridge University Press, 2011)
An aging population is best served by social, personal, and health support focused on maintaining and maximizing personal independence. The Internet affords numerous opportunities for individuals of all ages to communicate, access information, and engage in recreational activities. A community-based sample of 122 adults over 60 years of age completed a questionnaire which assessed three clusters of characteristics: (a) frequency and patterns of Internet use, (b) well-being (loneliness, life satisfaction, self-efficacy, social support, and depression), and (c) demographics (age, income, education). Significant correlations emerged between the three clusters of measured variables. Controlling for demographic differences, Internet use and self-efficacy remained significantly related. Among the sample of older adults, individuals who used the Internet more had higher perceptions of self-efficacy than those who used the Internet rarely or not at all.